2013
DOI: 10.1017/s0029665113003583
|View full text |Cite
|
Sign up to set email alerts
|

Dietary n-3 PUFA and CVD: a review of the evidence

Abstract: Many clinical and epidemiological studies have shown that the polyunsaturated n-3 fatty acids EPA and DHA from fish and fish oils, provide cardiovascular protection, particularly in the setting of secondary prevention. n-3 Fatty acids beneficially influence a number of cardiometabolic risk factors including blood pressure, cardiac function, vascular reactivity and lipids, as well as having anti-platelet, anti-inflammatory and anti-oxidative actions. They do not appear to adversely interact with other medicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 86 publications
2
44
0
Order By: Relevance
“…They inhibit pro-inflammatory cytokine production, increase antiinflammatory cytokine synthesis, and activate specific G-coupled protein receptors on neutrophils and macrophages to enhance clearance of cellular debris that is required for tissue homeostasis to be re-established [11,12]. n-3 fatty acids have been associated with cardiovascular protection and improve cardiovascular disease risk factors such as blood pressure, plasma triglycerides and inflammation [13,14]. We have also shown that n-3 fatty acid supplementation results in elevated levels of SPMs in healthy volunteers [15,16] suggesting that they may contribute to altered immune function.…”
Section: Introductionmentioning
confidence: 99%
“…They inhibit pro-inflammatory cytokine production, increase antiinflammatory cytokine synthesis, and activate specific G-coupled protein receptors on neutrophils and macrophages to enhance clearance of cellular debris that is required for tissue homeostasis to be re-established [11,12]. n-3 fatty acids have been associated with cardiovascular protection and improve cardiovascular disease risk factors such as blood pressure, plasma triglycerides and inflammation [13,14]. We have also shown that n-3 fatty acid supplementation results in elevated levels of SPMs in healthy volunteers [15,16] suggesting that they may contribute to altered immune function.…”
Section: Introductionmentioning
confidence: 99%
“…n-3 PUFAs are essential unsaturated fatty acids in humans and play a pivotal role on human health, conferring protective effects on patients with cardiovascular diseases [26,27,28]. n-3 PUFAs have been widely used in many chronic cardiovascular diseases due to there being no interactions with medicine and agents for the treatment of hypertension, hyperlipidemia, and platelet aggregation [29,30]. However, n-3 PUFAs are not synthesized in the human body and can only be absorbed from dietary sources such as fish and fish oil or transformed from assimilated α-linolenic acid [31].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the administration of n-3 PUFAs reduced the incidence of adverse cardiovascular events through their beneficial antihyperlipidemic, anti-inflammatory, antioxidative, antiarrhythmic, and anticoagulation effects [5,6,7]. Randomized clinical controlled trials have also shown that n-3 PUFAs not only protected the vascular function in DM, but also reduced the incidence of DM [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Some meta-analysis and reviews have attributed this discrepancy to the variability of several critical factors, like dosage, sample size, timing and duration of the treatment and the patient's selection criteria [18][19][20]. Althought some data have demonstrated the diminution of arterial tension (AT) with n-3 PUFAs in the essential hipertension [18,21,22], it was suggested that the supplementation with diet could be more appropriate in the prevention strategies than in the AHT treatment [18]. Nutritional supplements rich in n-3 PUFAs can decrease the AT.…”
Section: Introductionmentioning
confidence: 99%